PENGARUH BEBAN OPERASIONAL DAN PENDAPATAN TERHADAP KINERJA RETURN ON ASSET PADA PERUSAHAAN SEKTOR INDUSTRIAL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE (2020-2023) - WahyuDjati, Dendy Vercelly; Isnawati, Isnawati; Sarwani, Sarwani; Fitriaty, Diah; Fatimah, Fatimah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
By looking at data from industrial companies listed on the Indonesia Stock Exchange, this study found that financial performance increases as operating costs increase, and conversely, financial performance decreases as revenue increases. This research method is quantitative research with descriptive analysis techniques. The unit of analysis used is secondary data in the form of annual reports with data collection techniques, namely in the form of documentation of financial reports of industrial sector companies accessed through the website www.idx.co.id. The analysis technique used in this research is multiple linear regression analysis using the SPSS 26 for windows application. The number of samples in this study amounted to 24 industrial sector companies with a total observation of 4 years (2020-2023) so that 96 research samples were obtained. The results of this study indicate that first, the operating expense variable has a positive effect on Return On Asset performance. Second, revenue shows a negative effect on Return On Asset performance.